2012
DOI: 10.1128/aac.06170-11
|View full text |Cite
|
Sign up to set email alerts
|

Broad Phenotypic Cross-Resistance to Elvitegravir in HIV-Infected Patients Failing on Raltegravir-Containing Regimens

Abstract: .5.01; Virco). A control group of patients failing on other regimens was similarly tested. Sixty-one samples were analyzed, 40 of which belonged to patients failing on RAL-containing regimens. Full RAL susceptibility was found in 20/21 controls, while susceptibility to EVG was diminished in 8 subjects, with a median fold change (FC) of 2. T he introduction of highly active antiretroviral therapy (HAART) has transformed the prognosis of HIV-positive patients, with dramatic improvements in survival. However, sel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
47
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(49 citation statements)
references
References 17 publications
(17 reference statements)
1
47
0
1
Order By: Relevance
“…DTG, RAL, and EVG have all been recommended as components for first-line therapy regimens in the most recent U.S. DHHS guidelines (13). Clinical data indicate that viruses resistant to the earlier INSTIs (RAL and EVG) have arisen (2,8,10). DTG and GSK1265744 are clearly differentiated as new INSTIs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…DTG, RAL, and EVG have all been recommended as components for first-line therapy regimens in the most recent U.S. DHHS guidelines (13). Clinical data indicate that viruses resistant to the earlier INSTIs (RAL and EVG) have arisen (2,8,10). DTG and GSK1265744 are clearly differentiated as new INSTIs.…”
Section: Discussionmentioning
confidence: 99%
“…INSTIs are now recognized as a safe and highly effective class of anti-HIV drugs (6). However, clinical resistance to RAL and EVG has been observed, and a high degree of cross-resistance between these two agents has been demonstrated (7,8,9,10,11,12). Furthermore, dosing of RAL is done twice daily, while once-daily administration of EVG requires a pharmacokinetic (PK) booster, such as ritonavir or cobicistat.…”
mentioning
confidence: 99%
“…Each of these pathways is defined by one or more substitutions at specific amino acid positions within the integrase coding region: Y143C or R (here denoted Y143C,R), Q148H,K,R, and N155H (8,(15)(16)(17)(18)(19). Cross-resistance between RAL and EVG has been described for the viruses containing Q148H,K,R and N155H substitutions (20)(21)(22). However, it has been reported that viruses containing amino acid changes at position 143 retain susceptibility to EVG (23).…”
mentioning
confidence: 99%
“…7 RAL has shown failure in the selection of mutations at integrase position Y143, Q148, or N155. 8 Elvitegravir (EVG) (GS-9137) 9 and dolutegravir (DTG) (S/GSK-1349572) 10 are recently approved drugs along with INSTIs, which show improved efficacies against RAL resistant strains ( Figure 1 18 In line with continuous search for a better integrase inhibitor, we have selected dihydroisoquinoline as pharmacophore with a combination of nucleophiles having differential ability to chelate with Mg 2+ ions. Based on these facts, we designed and synthesized three types of 1,2-dihydroisoquinolines derivatives bearing different functional groups at the C-1, C-3, C-7, and N-2 positions (Figure 2).…”
mentioning
confidence: 99%